Line inductance measurement by using commutation time in line commutated converters - Sarul, Mustafa Hadi (SPRINGER, 2009)
Finding line inductance using wiring diagrams of the network is usually difficult or even impossible. In general, line inductance has to be measured in a simple nondisruptive way without service interruption. Several line inductance measurement techniques have been suggested previously, but they suffer from a number of limitations. In this paper, a novel line inductance measurement technique that uses the current commutation in a line-commutated converter is proposed. An expression for the line inductance as a function of phase-to-phase voltage, utility angle frequency, load current, triggering angle alpha and commutation time is procured. The line inductance is calculated by recording the commutating current waveforms by means of an accurate oscilloscope and measuring the other required values. Because of its simplicity, diode converter is employed in the experimental circuit when alpha = 0. The experiment is repeated for the case in which the phase inductances are different, and these phase inductances are calculated. To verify the performance of the proposed line inductance measurement technique, the known inductances are added in series to the line phase inductances. The results obtained show that the line inductance can be measured by the proposed measurement method precisely below 6% error. Finally, the error sources that may be encountered when the proposed method is applied are discussed.
Keywords: Inductance measurement; Converters; Power electronics; Power system measurements; Engineering